2008
DOI: 10.1007/s11104-008-9762-6
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of nutritional constraints on sweet potato (Ipomoea batatas) production in the central highlands of Papua New Guinea

Abstract: Sweet potato (Ipomoea batatas) is the staple food crop in the highlands of Papua New Guinea (PNG). Declining crop productivity, however, appears to be threatening the sustainability of sweet potato-based farming systems within the region, a probable cause being the exhaustion of soil nutrient reserves in continuously cultivated sweet potato gardens. To assess the extent of the problem, a survey of sweet potato gardens was conducted across four of the highlands provinces and information on soil and crop variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Further, smallholders often grow successive sweetpotato crops on a given area of land, leading to considerable yield differences compared with sweetpotato crops grown immediately after a fallow period. Differences result partly from soil and plant nutrition factors (Bailey et al, 2009;Hughes et al, 2009) but also from the build-up of pests and pathogens. Human population growth in less developed countries is also leading to an increase in cropping intensity with shorter fallow periods and more years of continuous cropping (Bourke, 2001).…”
Section: Sweetpotato and Food Security In Less Developed Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, smallholders often grow successive sweetpotato crops on a given area of land, leading to considerable yield differences compared with sweetpotato crops grown immediately after a fallow period. Differences result partly from soil and plant nutrition factors (Bailey et al, 2009;Hughes et al, 2009) but also from the build-up of pests and pathogens. Human population growth in less developed countries is also leading to an increase in cropping intensity with shorter fallow periods and more years of continuous cropping (Bourke, 2001).…”
Section: Sweetpotato and Food Security In Less Developed Countriesmentioning
confidence: 99%
“…This has the dual effect of further depleting soil nutrient levels and increasing the potential for pest and pathogen build-up . Associated with this, the adoption of strategies to manage nutrition, such as not burning crop residues (Bailey et al, 2009), can affect the carryover of pests and pathogen inocula. The build-up of pests and pathogens is exacerbated by the fact that sweetpotato is propagated vegetatively.…”
Section: Sweetpotato and Food Security In Less Developed Countriesmentioning
confidence: 99%
“…A small proportion of SPR is used as animal feed, but SPR has not yet been used on a mass-scale, because after microbial decomposition, it can easily pollute the environment. Bailey et al(2008) have found that SPR is a good source of dietary fibre (DF), containing more than 50% and can be categorised into soluble dietary fibre (SDF) or insoluble dietary fibre (IDF) (Zhang & Wang, 2013). Studies have shown that DF plays an important role in maintaining human health by preventing diseases such as coronary heart disease, colon cancer, obesity and diabetes (Esposito et al, 2005;Yang et al, 2006), with SDF appearing to be more effective than IDF (Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The SPR is mainly composed of residual starch and cellulose fibers (Bailey, Ramakrishna, & Kirchhof, 2009). After removing the residual starch, the content of cellulose fibers is about 75 wt.%.…”
Section: Introductionmentioning
confidence: 99%